Fiscal effects of aid - Timmis, Emilija (2015)
This thesis analyses fiscal effects of aid, first of health aid on health spending for a sample of developing countries and then broadly for Ethiopia and Tanzania. Particular attention is paid to data quality and the severe difficulties in achieving a reliable disaggregation of aid into its on-budget and off-budget components. The first essay assesses the sensitivity of estimated health aid fungibility to how the missing data (often considerable) are treated and explores a novel (at least in economics) method of multiple imputation. The second essay provides a conceptual framework for the disaggregation of (sector) aid into its on-budget and off-budget components. Given that complete binary distinction is not feasible, the aid-spending relationship is explored from a broader fiscal effects angle. This yields new insights on assessing the effect of health aid on health spending.